The Influence of Use of Google Classroom Media on Indonesian Language Learning Outcomes of Class Xi Students of SMKN 2 Sidrap - M Andri; Usman M; Hasanuddin; Sam Hermansyah; M Hijaz Tahir (International Journal of Sustainable Applied Sciences, 2023)
This research uses a quantitative approach method and a type of experimental research which aims to test the influence of Google Classroom media on Indonesian language learning outcomes for class XI SMK Negeri 2 Sidenreng Rappang. The population in this study was all class There are 2 variables in this study, namely the independent variable, the influence of Google Classroom media (x), while the dependent variable is the results of learning Indonesian in class XI (y). This research was carried out in class XI of SMK Negeri 2 Sidrap. Data collection techniques use documentation and tests. The test result data that has been collected is then analyzed using the t-test formula. Based on the results of data analysis, the experimental group score = 85.067 and the control group score = 77.714 and in the t.test the Tcount was 2.833 > from Ttable 5% (2.052) with db 27. Based on the research results it can be concluded that the use of Google Classroom media has an impact on Indonesian language learning results for class XI students at SMK Negeri 2 Sidrap.